Green Service and Customer Satisfaction in the Nepalese Hotel Industry: A Path to Sustainable Hospitality - Anurag Gaihray; Kriti Kriti (Darul Yasin Al Sys, 2026)
Sustainable practices in the hospitality industry are increasingly recognized as key drivers of customer satisfaction and loyalty, yet in Nepal empirical evidence on how green service practices shape guest experiences in hotels remains limited. This study aims to examine the perceptions of foreign customers regarding green service initiatives in major Kathmandu hotels and to analyze the relationship between green service and customer satisfaction. Employing a descriptive and causal-comparative design, data were collected from 73 foreign guests using structured questionnaires. The findings indicate that guests perceive green service initiatives, such as the use of sustainable materials, energy-efficient operations, waste management practices, and locally sourced ingredients—positively, and overall customer satisfaction was high, with most respondents expressing intentions to revisit and recommend the hotels. Statistical analyses revealed a significant positive relationship between green service and satisfaction (Kendall’s τ = .334, p < .01), and regression results confirmed that green service significantly predicts customer satisfaction (β = .378, p = .001), explaining 24.3% of the variance. The study concludes that green service practices constitute an important driver of customer satisfaction in Nepalese hotels, enhancing guest experiences while supporting sustainable hospitality development, and provides early empirical evidence in the Nepalese context to inform hotel managers seeking to integrate sustainability with service excellence.